Building a sustainable ecosystem of human resource management research: reflections and suggestions1. Issue 3 (4th February 2023) - Cooke, Fang Lee; Dickmann, Michael; Perry, Emma
Abstract: In this annual editorial for The International Journal of Human Resource Management, we project a vision of a sustainable ecosystem of human resource management (HRM) research by reflecting on key trends of HRM research and provide suggestions for future research efforts for the HRM research community. We outline the evolution and development of six areas of HRM research that are highly relevant to the policy and practice in the current global political-economic context. These research pursuits are shifting from firm-oriented and technology-oriented to becoming more employee-oriented and society-oriented. We extend these lines of enquiry with suggestions of what future research can examine to keep pace with practice and to offer policy and practical recommendations. We argue that different sub-fields of HRM research can complement, reinforce and interact with each other to enable us to build a robust and expanding research programme, intellectually and practically, to reflect the world of work and to demonstrate the relevance of our research to society with scientific rigour.